2020
DOI: 10.1021/acs.jpclett.0c00161
|View full text |Cite
|
Sign up to set email alerts
|

All-Inorganic Copper Halide as a Stable and Self-Absorption-Free X-ray Scintillator

Abstract: Lead halide perovskites have recently shown great potential as X-ray scintillators; however, the toxicity of the lead element seriously restricts their applications. Herein we report a new lead-free and self-absorption-free scintillator based on Rb 2 CuCl 3 metal halide. The Rb 2 CuCl 3 exhibits a near-unity photoluminescence quantum yield (99.4%) as well as a long photoluminescence lifetime (11.3 μs). Furthermore, Rb 2 CuCl 3 demonstrates an appreciable light yield of 16 600 photons per megaelectronvolt and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
165
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(177 citation statements)
references
References 45 publications
11
165
1
Order By: Relevance
“…As shown in Fig. 2c, the light yield of (C 38 H 34 P 2 )MnBr 4 is comparable to those of recently reported lead-free metal halides, such as Cs 3 Cu 2 I 5 (79,279 photon MeV −1 ) 43 and Rb 2 CuBr 3 (91,056 photon MeV −1 ) 33 , and much better than those of Rb 2 CuCl 3 (16,600 photon MeV −1 ) 34 , widely investigated CsPbBr 3 nanocrystals (21,000 photon MeV −1 ) 22 , and many commercially available scintillators, such as CsI:Tl (54,000 photon MeV −1 ) and CdWO 4 (28,000 photon MeV −1 ). Moreover, based on the toxicity classification (health and environment) information of metal halides from material safety data sheet, (C 38 H 34 P 2 )MnBr 4 is believed to be significantly less toxic than existing scintillators mentioned above.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…As shown in Fig. 2c, the light yield of (C 38 H 34 P 2 )MnBr 4 is comparable to those of recently reported lead-free metal halides, such as Cs 3 Cu 2 I 5 (79,279 photon MeV −1 ) 43 and Rb 2 CuBr 3 (91,056 photon MeV −1 ) 33 , and much better than those of Rb 2 CuCl 3 (16,600 photon MeV −1 ) 34 , widely investigated CsPbBr 3 nanocrystals (21,000 photon MeV −1 ) 22 , and many commercially available scintillators, such as CsI:Tl (54,000 photon MeV −1 ) and CdWO 4 (28,000 photon MeV −1 ). Moreover, based on the toxicity classification (health and environment) information of metal halides from material safety data sheet, (C 38 H 34 P 2 )MnBr 4 is believed to be significantly less toxic than existing scintillators mentioned above.…”
Section: Resultssupporting
confidence: 84%
“…As shown in Supplementary Table 3, Pb(II), Cu(I), CsI, and GdWO 4 possess the most severe toxicity in the environment, and Tl(I) and CsI are moderately toxic to health. Also, 87 Rb isotope is radioactive 34 . Mn(II) is considered to be less toxic for health and friendly to the environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the decay lifetime values, it would be noted here that such self‐trap state (STS) related emissions might have shorter and longer lifetime. [ 7a,8b,9a,15 ] For better understanding, fitted data in all our halides were also analyzed (Table S10, Supporting Information) and it was clear that in all cases a longer component having few hundred nanoseconds lifetime were also associated. However, the average lifetime was reduced due to larger contribution of fast decay component.…”
Section: Figurementioning
confidence: 99%
“…Referring to the problem of lead, Tang et al developed a new copper-based scintillator with ultrahigh LY. 22,23 Whereas, the emission peak locates in the UV region, which is not consistent with the response of PVDs. Kovalenko et al reported the fabrication of zero-dimensional tin (Sn 2+ ) halides and achieved relatively high LY and long-wavelength emission (660 nm) simultaneously.…”
Section: Main Textmentioning
confidence: 91%